Acute alcohol exposure induces reproductive behavior defects, subfertility, brain transcriptomic changes of parental zebrafish and malformation in their offspring - Li Peng; Jun-Yuan Lei; Yue-Ying Meng; Shang-Chun Li; Xiang-Yan Dai (Toxicology, 2026)

Precision omic portrait deciphers the epigenetic variable during cellular identity reshaping of metastatic head and neck squamous cell carcinoma - Qiushi Feng; Xiaofeng Shan; Yangyang Xia; Lingzi Liao; Yifan Kang; Zimeng Li; Ziwei Dai; Yingyue Chai; Xinyuan Zhang; Luming Wang; Shang Xie; Zhigang Cai (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Changes of canopy nitrogen distribution and nitrogen metabolism in hybrid rice under global dimming: A three-year field study - Liying Huang; Fangfang Hou; Wanting Li; Liyan Shang; Shuaijun Dai; Chunhu Wang; Ke Liu; Zhaoqiang Jin; Shijie Shi; Xiaohai Tian; Yunbo Zhang (European Journal of Agronomy, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dual-atom catalysts on defective boron nitride for bifunctional ammonia and urea synthesis - Dongyue Gao; Lijun Shang; Junxia Li; Yadong Yu; Mengyan Dai; Yi Fang; Yang Huang; Chengchun Tang; Zhonglu Guo (Fuel, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

The Synergistic Role of ApoE4 and GSK3β in Alzheimer’s Disease: Pathological Mechanisms and Therapeutic Implications - Qianwei Li; Yinghui Shang; Han-Chang Huang; Xueling Dai; Fengxue Lao (Molecular Neurobiology, 2026)

Alum-Enhanced MICP for Sand Stabilization: Mechanisms and optimization - Zhiyang Shang; Jie Peng; Renjie Wei; Liangliang Li; Zhao Jiang; Di Dai (Sustainable Chemistry and Pharmacy, 2025)

Integration of Sentinel-1 and 2 for estimating soil organic carbon content in reclaimed coastal croplands with novel indices - Jianjun Wang; Jingjing Huang; Yun Zhang; Jiali Shang; Quan Yin; Weilong Li; Lige Cao; Guisheng Zhou; Pei Sun Loh; Qigen Dai (Soil and Tillage Research, 2025)

Efficient room-temperature hydrolytic cleavage of CS2 via Pd-anchored polynitrogen porous polymers - Kai-Wen Jiang; Xing-Yu Chen; Xiao-Li Jiang; Qing-Ya Sun; Yu-Peng Dai; Hui-Zhen He; Ying Zhou; Ping Shang; Xuan-Feng Jiang (Journal of Hazardous Materials, 2025)

Origin and preservation of Li and Se–Mo–U in Carboniferous-Permian coals from the Jincheng Coalfield, Qinshui basin, Shanxi Province, China - Mengda Yao; Ian T. Graham; Shifeng Dai; David French; Shaowei Zhang; Jintian Zheng; Shuai Kang; Niande Shang; Doudou Li (Applied Geochemistry, 2025)

Design and mechanism of ultra-flexible commercial solid-state lithium batteries over 10,000 dynamic bending cycles - Long Zhang; Kaixuan Zhou; Xinke Dai; Zhen Shang; Changjun Lu; Jun Li; Guoyong Huang; Shengming Xu (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of synthetic microbial community fermentation on volatile flavor and quality characteristics of ginger pickle - Yankai Min; Qing Zhang; Jiali Liu; Yanling Shang; Yilin Hou; Min Zhang; Jingwen Dai; Ziyu Li; Wenliang Xiang; Jie Tang (Food Research International, 2025)

Supramolecular lipopeptidic adjuvant regulates protective abilities of MPXV subunit vaccine against monkeypox virus - Wenxin Bao; Yanwen Zhang; Chao Shang; Zhedong Jin; Yilong Zhu; Lili Dai; Caixia Cui; Huiyi Li; Jiangbo Wei; Xiao Li; Jianwei Zhu; Yin Wang; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Effect of lead exposure on silkworm midgut: Insights into oxidative gene expression, digestive function, and microbial community structure - Yan-Xia Shi; Dan-Dan Bian; Fan-Xing Chen; Ye Jin; Qi Jiang; Qiu-Ning Liu; Bo-Ping Tang; Li-Shang Dai (Process Safety and Environmental Protection, 2024)

Unveiling the immune-modulating power of THz-FEL irradiation - Qi Zhang; Weijun Wang; Sen Shang; Xu Li; Tingting Zhao; Peng Zhang; Dai Wu; Kui Zhou; Xiaoyun Lu (Journal of Photochemistry and Photobiology B: Biology, 2024)

In-situ surface reconstruction of CsPbl3 perovskite for efficient and stable solar cells - Weideren Dai; Yanzhuo Gou; Huili Wei; Chang Chen; Zexun Pan; Xu zhang; Liangyou Lin; Minghui Shang; Qunchao zhang; Xianbao Wang; Qidong Tai; Jinhua Li (Chemical Engineering Journal, 2024)

Integrated framework for dynamic conservation of bamboo forest in giant panda habitat under climate change - Xiaotong Shang; Weirui Qin; Biao Yang; Qiang Dai; Han Pan; Xuyu Yang; Xiaodong Gu; Zhisong Yang; Zejun Zhang; Li Zhang (Journal of Environmental Management, 2024)

Genome-wide association study reveals genetic loci for ten trace elements in foxtail millet (Setaria italica) - Hanxiao Liu; Xin Zhang; Yuping Shang; Shaoxing Zhao; Yingjia Li; Xutao Zhou; Xiaoyu Huo; Pengfei Qiao; Xin Wang; Keli Dai; Huixia Li; Jie Guo; et al. (Theoretical and Applied Genetics, 2024)

Effects of High-Water Fluoride Exposure on IQ Levels in School-Age Children: A Cross-Sectional Study in Jiangsu, China - Yuting Xia; Yan Xu; Ming Shi; Song Liu; Suwan Liu; Hui Wang; Chaoyong Dai; Yunjie Ye; Mao Liu; Li Shang; Yang Wang; Peihua Wang (Exposure and Health, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Transcriptome analysis of flower colour reveals the correlation between SNP and differential expression genes in Phalaenopsis - Yu Ding; Ma-Yin Wang; Ding-Hai Yang; Dai-Cheng Hao; Wei-Shi Li; Peng Ling; Shang-Qian Xie (Genes & Genomics, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Developing smart air purifier control strategies for better IAQ and energy efficiency using reinforcement learning - Wenzhe Shang; Junjie Liu; Congcong Wang; Jiayu Li; Xilei Dai (Building and Environment, 2023)

Juvenile hormone suppresses the FoxO-takeout axis to shorten longevity in male silkworm - Zhiquan Li; Jiangbo Song; Guihua Jiang; Yunzhu Shang; Yu Jiang; Jianfei Zhang; Li Xiao; Min Chen; Dongmei Tang; Xiaoling Tong; Fangyin Dai (Pesticide Biochemistry and Physiology, 2023)

Synthesis of γ-cyclodextrin metal-organic framework as ethylene absorber for improving postharvest quality of kiwi fruit - Suqing Li; Xinxin Hu; Shuyao Chen; Xiao Wang; Hengshuai Shang; Yuan Zhou; Jianwu Dai; Lan Xiao; Wen Qin; Yaowen Liu (Food Hydrocolloids, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Application of controlled-release urea to maintain rice yield and mitigate greenhouse gas emissions of rice–crayfish coculture field - Qiang Xu; Linxiu Dai; Ziyin Shang; Ying Zhou; Jingyong Li; Zhi Dou; Xiaochun Yuan; Hui Gao (Agriculture, Ecosystems & Environment, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

An alanine to valine mutation of glutamyl-tRNA reductase enhances 5-aminolevulinic acid synthesis in rice - Meng Jiang; Shang Dai; Yun-Chao Zheng; Rui-Qing Li; Yuan-Yuan Tan; Gang Pan; Ian Max Møller; Shi-Yong Song; Jian-Zhong Huang; Qing-Yao Shu (Theoretical and Applied Genetics, 2022)

Expansion of bilin‐based red light sensors in the subaerial desert cyanobacterium Nostoc flagelliforme - Hai‐Feng Xu; Guo‐Zheng Dai; Yu‐Jie Wang; Chao Cheng; Jin‐Long Shang; Ren‐Han Li; Ke Liu; Deqiang Duanmu; Bao‐Sheng Qiu (Environmental Microbiology, 2022)
Summary Light is the crucial environmental signal for desiccation‐tolerant cyanobacteria to activate photosynthesis and prepare for desiccation at dawn. However, the photobiological characteristics of desert cyanobacteria adaptation to one of the harshest habitats on Earth remain unresolved. In this study, we surveyed the genome of a subaerial desert cyanobacterium Nostoc flagelliforme and identified two phytochromes and seven cyanobacteriochromes (CBCRs) with one or more bilin‐binding GAF (cGMP phosphodiesterase/adenylyl cyclase/FhlA) domains. Biochemical and spectroscopic analyses of 69 purified GAF‐containing proteins from recombinant phycocyanobilin (PCB), biliverdin or phycoerythrobilin‐producing Escherichia coli indicated that nine of these proteins bind chromophores. Further investigation revealed that 11 GAFs form covalent adducts responsive to near‐UV and visible light: eight GAFs contained PCB chromophores, three GAFs contained biliverdin chromophores and one contained the PCB isomer, phycoviolobilin. Interestingly, COO91_03972 is the first‐ever reported GAF‐only CBCR capable of sensing five wavelengths of light. Bioinformatics and biochemical analyses revealed that residue P132 of COO91_03972 is essential for chromophore binding to dual‐cysteine CBCRs. Furthermore, the complement of N . flagelliforme CBCRs is enriched in red light sensors. We hypothesize that these sensors are critical for the acclimatization of N . flagelliforme to weak light environments at dawn.

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Technical methodologies for the assessment of the impacts of reclamation projects on marine ecology - Yurong Ouyang; Lin Wu; Juanjuan Dai; Yaojian Wu; Ling Cai; Qingsheng Li; Jianwei Wu; Shang Jiang (Environmental Science and Pollution Research, 2022)

Genomic Analysis of the Principal Members of Antioxidant Enzymes in Simulated Stresses Response and Postharvest Physiological Deterioration in Cassava - Sang Shang; Yuqi Tang; Jing Dai; Chunlai Wu; Yan Yan; Weiwei Tie; Meiying Li; Jinghao Yang; Jian Zeng; Mingjie Chen; Wei Hu (Tropical Plant Biology, 2021)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

Autoinducer-2 signaling is involved in regulation of stress-related genes of Deinococcus radiodurans - Lin Lin; Tao Li; Shang Dai; Jiangliu Yu; Xiuqin Chen; Liangyan Wang; Yunguang Wang; Yuejin Hua; Bing Tian (Archives of Microbiology, 2016)

High-level expression of bioactive recombinant human lysozyme in the milk of transgenic mice using a modified human lactoferrin BAC - Shen Liu; Xiangqing Li; Dan Lu; Shengzhe Shang; Meili Wang; Min Zheng; Ran Zhang; Bo Tang; Qiuyan Li; Yunping Dai; Ning Li (Transgenic Research, 2012)

Thidiazuron-induced somatic embryos, their multiplication, maturation, and conversion in Cinnamomum pauciflorum Nees (Lauraceae) - L. Kong; D. Dai; M. Shang; K. Li; C.-X. Zhang (New Forests, 2009)